PELATIHAN BAHASA INGGRIS DASAR DENGAN METODE LEARNING BY DOING BAGI ANAK NELAYAN DI PESISIR PANTAI SIRE, LOMBOK UTARA - NTB - Etika Ariyani (Bajang Institute, 2023)
This community service program aims to equip basic English for fisherman’s children at Sire coast, North Lombok – West Nusa Tenggara Province. This training held for ten weeks, twice a week with time allocation 60 minutes for every session. Topics in this training consists of introducing language functions such as greeting, asking permission, asking direction, apologizing, requesting, explaining something or someone and offering something. Participants consists of 16 (sixteen) fisherman’s children which lived near Sire coast. This program used learning by doing mehod which covering orientation, discussion, demonstration, feedback and repetition. Learning by doing method aroused the children motivation to learn English by direct experiences not only demonstrating or telling. Data collected from tests ( orally - writtenly) and interview. Participants performance measured by using criterion referenced tests, based on the result of the evaluation which covered three language function showed that there are 12 participants (75%) got A (80 – 100) and only 4 participants (25%) got B (65 – 79). It means that there are no participants got score under minimum criterion (65). The result of the program indicated that there is an improvement at their English performance significantly, we can concluded that the implementation of learning by doing method in learning English effective